(Keynote) Devices in CMOS for Terahertz Circuits and Systems. (1st August 2017) - O, Kenneth K.; Ahmad, Zeshan; Choi, Wooyeol; Sharma, Navneet; Zhang, Jing; Zhong, Qian; Kim, Dae-Yeon; Chen, Zhiyu; Zhang, Yaming; Han, Ruonan; Shim, Dongha; Sankaran, Swaminathan; et al.
Abstract : CMOS (Complementary Metal Oxide Silicon) integrated circuits (IC's) technology has emerged as a means for realization of capable and affordable systems that operate at 300 GHz and higher. Signal generation up to 1.3 THz and coherent detection up to 410 GHz and incoherent detection up to 10 THz have been demonstrated using CMOS integrated circuits. Furthermore, a highly integrated rotational spectroscopy transceiver operating up to near 300 GHz and imaging arrays operating near 1 THz have been demonstrated in CMOS. Signal generation as well as coherent detection up to 5 THz as well as incoherent detection beyond 40 THz with sufficient performance for practical applications should be possible in CMOS especially with minor process modifications to optimize the performance of MOS varactors and Schottky barrier diodes.